Intensive Local Radiotherapy Is Associated With Better Local Control and Prolonged Survival in Bone-Metastatic Nasopharyngeal Carcinoma Patients - Li, Xiao-Yun; Jia, Guo-Dong; Sun, Xue-Song; Guo, Shan-Shan; Liu, Li-Ting; Liu, Sai-Lan; Yan, Jin-Jie; Luo, Dong-Hua; Sun, Rui; Guo, Ling; Mo, Hao-Yuan; Tang, Lin-Quan; et al. (Frontiers in Oncology, 2020)
Objective: To compare the survival outcomes brought by different radiation dose schedules to bone lesions and different chemotherapy regimens in bone metastatic nasopharyngeal carcinoma (NPC). Background: The current treatment strategy for bone metastatic NPC patients was empirically given and poorly studied before. It is of necessity to optimize the treatment for bone metastasis to enhance the therapeutic effect and increase the proportion of long-term survived patients. Methods: 300 patients who received chemoradiotherapy from 2002 to 2018 were involved in the study. Demographics, laboratory results and detailed treatment plans were recorded. Radiotherapy plans were classified into three categories based on the intensity, and the survival analysis was performed using log-rank test. Multivariable analysis was made by the Cox proportional regression model. Results: Patients who received 60-75 Gy/ 30-35 fractions of radiation to the metastatic bones had significantly longer bone relapse-free survival (BRFS) (HR, 0.53, 95%CI, 0.37-0.78, P=0.003), overall survival (OS) (HR, 0.63, 95%CI, 0.46-0.84, P=0.007) and progression-free survival (PFS) (HR, 0.80, 95%CI, 0.67-0.95, P=0.041). The administration of paclitaxel, cisplatin and 5-fluorouracil regimen was also associated with better BRFS (HR, 0.27, 95%CI, 0.10-0.75, P=0.007), PFS (HR, 0.60, 95%CI, 0.42-0.87, P=0.007), and OS with borderline significance (HR, 0.54, 95%CI, 0.29-1.03, P=0.058). In multivariable analysis, the post-treatment EBV DNA level and radical radiation dose were proved as independent prognostic factors for both BRFS and OS. Conclusions: Radiotherapy to metastatic bones with palliative dose prescription should not be considered in bone metastatic NPC patients. TPF chemotherapy regimen might help to improve the survivals in NPC patients but failed to be an independent protective factor.